Upaya Pengembangan Diri Siswa melalui Layanan Bimbingan dan Konseling Sekolah Menengah Atas di Provinsi Banten - Salman Tumanggor (Indonesian Journal of Educational Counseling, 2020)
SELF-STUDENTS DEVELOPMENT BY GUIDANCE AND COUNCELING SERVICE IN HIGH SCHOOL AT BANTEN PROVINCE. Guidance and counseling program organized to support the achievement of the educational objectives of the school as a whole. The based goal is essentially to prepare students through guidance, teaching, and training for their roles in the future. The efforts of self-development especially the high school student are the principal leadership approach to motivated the resources in school the are guidance and counseling teacher performance specifically services to the students and technical facilities as a media to help guidance and counseling teacher directed students to make their decisions. The purpose of this research is to know the relationship of principal leadership, teacher performance guidance counseling and a technical facility with self-students development. This research uses descriptive analysis method of correlation with the quantitative approach. Data collection by questionnaires. The sample used purposive sampling at senior high school in Banten province. The results show a relationship principal leadership with self-students development, guidance and counseling teacher performance with self-students development, technical facility with self-students development, the relationship of principal leadership, guidance and counseling teacher performance and technical facilities with self-students development. The effort of self-students development can be improving by principal leadership, guidance, and counseling teacher performance and technical facilities.